Ependymoma: an epidemiological perspective from a low- and middle-income country - Muhammad Usman Khalid; Mashal Murad Shah; Mohammad Hamza Bajwa; Karim Rizwan Nathani; Altaf Ali Laghari; Muhammad Faraz Raghib; Saad bin Anis; Naveed Zaman Akhunzada; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To enumerate the burden of ependymoma in our region and identify the demographic, tumoural, surgical, clinical characteristics, and outcomes of patients diagnosed with ependymoma. Methods: This retrospective cross-sectional study included patients admitted under neurosurgical service between January 1 and December 31, 2019. The inclusion criterion for the study was a histopathological diagnosis of the brain lesion. The experience of the ependymal brain tumours observed at the 32 participating sites in Pakistan is presented. Results: A total of 2750 patients with brain tumours were seen in 2019 at our centres of whom 58(2.1%) had a histopathological diagnosis of ependymoma. The median age at diagnosis was nine (IQR= 4.5-24.5) years. The median time to surgery from date of radiological diagnosis was 38.5 (IQR= 4-93.8) days. The median KPS score at presentation was 70 (IQR= 60-80), and post-surgery was 90 (IQR= 70-100), showing an average increase of 20. Our population's overall mortality rate for ependymoma was 31.1%, with the 30-day mortality rate being 2.2% (lower than the 4.5% on average for all brain tumours in our cohort). Conclusion: Ependymomas were predominantly found in the paediatric population in the presented cohort. While gender distribution and histopathological grading seemed to follow international trends, this study had a much higher mortality rate and a much lower gross total resection rate than centres in high-income countries. Keywords: Ependymoma, Brain neoplasm, Retrospective study, Epidemiology, LMIC. Continue...